Phylogenetic Lineages of Francisella tularensis in Animals - Pilo, Paola (Frontiers in Cellular and Infection Microbiology, 2018)
Tularemia is a zoonotic disease caused by the facultative intracellular bacterium Francisella tularensis. This microorganism can infect a plethora of animal species and its ecology is particularly complex. Much research was performed to understand its biology but many questions are still open, especially concerning the life cycle of this bacterium in the environment related to physical and biological parameters. Numerous animals are major hosts of F. tularensis but precise reservoir species are not yet well defined. Moreover, the exact range of species susceptible to tularemia is not clear and is complicated by the differences in virulence and ecology observed among the subspecies of F. tularensis. Indeed, different life cycles in nature, including the animal species concerned, were previously described for F. tularensis subsp. tularensis and F. tularensis subsp. holarctica. Recently, molecular techniques showing adequate discrimination between strains were developed, leading to the possibility to investigate links between phylogenetic lineages and infection in animals. New perspectives in research are now possible thanks to the information available and the simplicity of the molecular procedures. Current studies are unfolding the evolution of F. tularensis and these developments will lead to the elucidation of geographical and ecological differences observed by veterinarians, microbiologists and conservation biologists. However, systematic, coordinated collection of data and extensive sampling are important to efficiently assemble the findings of future research.